Biomedical titanium alloy surface modification method

Through femtosecond laser processing, alkaline heat treatment, polydopamine layer coating and silver ion loading, titanium alloy materials with excellent biological activity and antibacterial ability were prepared, solving the problems of insufficient biological activity, poor bone integration and bacterial infection in bone implant applications.

CN119506873AActive Publication Date: 2025-02-25BEIJING INST OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411444159.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-25
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

Biomedical titanium alloys have problems such as low biological activity, poor bone integration and bacterial infection in bone implant applications.

Method used

The multi-step collaborative treatment method of femtosecond laser processing, alkaline heat treatment, polydopamine layer coating and silver ion loading was prepared to improve the bioactivity and antibacterial ability of the material.

Benefits of technology

It significantly improves the integration ability of biomedical titanium alloy materials with bone tissue and anti-bacterial infection ability, providing excellent cell compatibility and drug-carrying ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506873A_ABST
    Figure CN119506873A_ABST
Patent Text Reader

Abstract

The invention relates to a biomedical titanium alloy surface modification method, and belongs to the technical field of laser application. The method comprises the following steps: firstly, machining a groove-micro-ripple composite structure on the surface of a clean and polished nickel-titanium alloy material by using femtosecond laser; then, rich nanosheets are formed on the basis of the structure through alkali heat treatment, and a groove-micro ripple-nanosheet multistage micro-nano composite structure is obtained; then, the multi-stage micro-nano composite structure is put into an alkaline Tris buffer solution containing dopamine hydrochloride to be coated with a polydopamine coating; and finally, the multi-stage micro-nano composite structure coated with the polydopamine coating is placed in a silver nitrate solution to load silver ions, surface modification of the titanium alloy is completed, and the biological activity, the osseointegration capacity and the bacterial infection resistance of the titanium alloy are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a surface modification method of a biomedical titanium alloy and belongs to the technical field of laser application. Background Art

[0002] Titanium alloys, especially nickel-titanium alloys, have been widely used in the biomedical field, especially as bone implant materials, due to their good mechanical properties, corrosion resistance and biocompatibility. However, traditional titanium alloy materials still face key problems in bone implant applications, such as insufficient bioactivity, poor bone integration and easy bacterial infection.

[0003] In order to solve these problems, researchers are constantly exploring new surface modification technologies to enhance the performance of titanium alloy materials. Among them, femtosecond laser processing technology shows great potential in material surface modification due to its high precision, high energy density and non-contact processing characteristics. Femtosecond laser can create complex micro-nano structures on the surface of materials. These structures can significantly increase the specific surface area of ​​the material and promote the interaction between cells and the surface of the material, thereby enhancing the bioactivity and bone integration ability of the material. On the other hand, alkali heat treatment, as another effective surface modification method, has also been widely studied and applied to improve the biocompatibility of titanium alloy materials. Alkali heat treatment can improve the surface chemical properties of the material, increase the hydrophilicity of the material, and help further promote the adhesion and proliferation of cells on the surface of the material by treating the material in a high temperature alkaline environment. In addition, alkali heat treatment can also introduce more functional groups on the surface of the material, providing favorable conditions for subsequent coating or loading treatment.

[0004] In existing research, for example, Liang Chunyong proposed a method of enhancing the bioactivity of titanium surface by combining femtosecond laser with alkali treatment, but it focused on the bone bonding ability of the material and did not pay specific attention to the material's anti-bacterial infection function. Guan Yingchun et al. proposed a method for preparing antibacterial surfaces on medical devices inserted into the body, using ultrafast laser-induced micro-nano structures to prepare hydrophobic antibacterial adhesion surfaces. Then, metal nanoparticles such as copper were deposited using a coating process to prepare a bactericidal film, and finally an antibacterial surface was obtained. However, the surface prepared by this method is not conducive to cell adhesion, and does not specifically focus on the osteogenic ability of bone implant applications and the bioactivity of the material. At present, there is still a lack of a titanium alloy surface modification method with excellent comprehensive performance, simple process, and easy control. In particular, for the application of biomedical titanium alloys in bone implants, a surface modification technology that can not only improve bioactivity, significantly improve the ability to integrate with bone tissue, but also effectively prevent bacterial infection is needed.

[0005] Therefore, the present invention proposes a titanium alloy surface modification method combining femtosecond laser processing, alkali heat treatment, polydopamine layer coating and silver ion loading, aiming to prepare a biomedical titanium alloy material with excellent bioactivity and antibacterial ability through multi-step coordinated treatment, so as to solve the problems of low bioactivity, poor bone integration and bacterial infection existing in the current titanium alloy application in bone implants. Summary of the invention

[0006] The purpose of the present invention is to solve the problems of low biological activity, poor bone integration and bacterial infection in the application of biomedical titanium alloy in bone implants; to provide a surface modification method of biomedical titanium alloy; the implementation of the method of the present invention includes four core steps: femtosecond laser processing, alkali heat treatment, polydopamine layer coating and silver ion loading. The present invention first uses a femtosecond laser to process a groove-micro-ripple composite structure on the surface of a clean and polished nickel-titanium alloy material; then, alkali heat treatment is performed to form rich nanosheets on the basis of the structure to obtain a groove-micro-ripple-nanosheet multi-level micro-nano composite structure; subsequently, the multi-level micro-nano composite structure is placed in an alkaline Tris buffer containing dopamine hydrochloride and coated with a polydopamine coating; finally, the multi-level micro-nano composite structure coated with the polydopamine coating is placed in a silver nitrate solution to load silver ions. Femtosecond laser and alkaline heat treatment improve the biological inertness of titanium alloys, enhance the hydrophilicity of the material, promote the adhesion of osteoblasts to the material, and improve the integration ability of biomedical titanium alloy materials with bone tissue; polydopamine layer coating and silver ion loading treatment enhance the ability of biomedical titanium alloy materials to resist bacterial infection, so that it can be used to improve the performance of bone implants.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] A method for modifying the surface of a biomedical titanium alloy comprises the following steps:

[0009] Step 1: Ultrasonic cleaning and drying of the polished nickel-titanium alloy material.

[0010] Step 2: Use multiple mirrors to guide the femtosecond laser to the surface of the nickel-titanium alloy material to be processed, and focus it vertically to the surface of the nickel-titanium alloy material through an optical lens.

[0011] Step 3: Select a sapphire femtosecond laser processing system, set the femtosecond laser processing frequency, power, scanning speed, scanning spacing and other parameters, process at the focus, and ultrasonically clean and dry after processing.

[0012] Step 4: Place the nickel-titanium alloy sample with micro-nano surface structure prepared in step 3 into a high-temperature reactor, add appropriate concentration of alkali solution for alkaline heat treatment, and ultrasonically clean and dry after the treatment.

[0013] Step 5: Place the sample prepared in step 4 into an alkaline Tris buffer solution containing dopamine hydrochloride to form a polydopamine coating thereon.

[0014] Step 6: Place the sample prepared in step 5 into a silver nitrate solution to generate nanosilver thereon.

[0015] The specific implementation steps of step three are as follows:

[0016] (1) Load the glass slide with the clean nickel-titanium alloy material fixed on a high-precision six-degree-of-freedom translation stage.

[0017] (2) A sapphire femtosecond laser processing system is selected, the wavelength of the femtosecond laser is 800nm, a 5x processing objective lens is selected, the repetition rate of the femtosecond laser is set to 1000Hz, the processing power of the femtosecond laser is set to 8-30mW, the scanning speed is 500-2000um / s, the scanning interval is 8-20um, the processing is performed at the focus, and the processing is cleaned and dried after completion.

[0018] The specific implementation steps of step 4 are as follows:

[0019] Prepare an alkaline solution with a concentration of 1-5M composed of sodium hydroxide and deionized water, place the alkaline solution and the sample prepared in step 3 into a high-pressure reactor with polytetrafluoroethylene as the inner village, cover it tightly, then place the high-pressure reactor in a muffle furnace, set the reaction temperature to 80°, react for 12-24 hours, and clean and dry after the treatment.

[0020] The specific implementation steps of step five are as follows:

[0021] Select an alkaline Tris buffer with a pH value of 8 to 10 and use it as a solvent to prepare a dopamine hydrochloride solution with a concentration of 1 mg / ml to 3 mg / ml. Fully immerse the sample prepared in step 4 in the dopamine hydrochloride solution and let it stand for 12h to 24h. After the treatment, wash and dry.

[0022] The specific implementation steps of step six are as follows:

[0023] Prepare a silver nitrate solution with a concentration of 10mM-50mM, place the sample prepared in step 5 into the silver nitrate solution, and react for 1h-12h in a dark environment. After the treatment, wash and dry.

[0024] Beneficial effects:

[0025] 1. A biomedical titanium alloy surface modification method of the present invention can improve the ability of biomedical titanium alloy materials (such as nickel-titanium alloys) to integrate with bone tissue and their ability to resist bacterial infection.

[0026] 2. The biomedical titanium alloy surface modification method of the present invention, combined with the ability of patterned processing by utilizing a high-precision six-degree-of-freedom translation stage, can realize the processing of titanium alloy materials of various shapes and sizes.

[0027] 3. The biomedical titanium alloy surface modification method of the present invention can prepare a biomedical titanium alloy material with good hydrophilicity, excellent cell compatibility in vitro, no cytotoxicity, and can promote cell adhesion and proliferation.

[0028] 4. The surface modification method of a biomedical titanium alloy of the present invention can prepare a multi-level micro-nano composite structure of grooves, microripples and nanosheets, which can effectively inhibit the formation of biofilms. At the same time, combined with the bactericidal ability of nanosilver attached to the surface of the structure, the surface of the prepared material has excellent resistance to bacterial infection.

[0029] 5. The surface modification method of a biomedical titanium alloy of the present invention prepares a multi-level micro-nano composite structure of grooves-microripples-nanosheets with a high specific surface area, can provide abundant drug loading space, and has excellent drug loading capacity.

[0030] 6. A biomedical titanium alloy surface modification method of the present invention, the groove-microripple-nanosheet multi-level micro-nano composite structure biomedical titanium alloy material preparation method is flexible and simple, the process parameters are easy to control, and it is easy to realize application in the field of laser technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the optical path diagram of the femtosecond laser processing of the present invention.

[0032] Figure 2 The following are SEM images of materials prepared by the embodiments of the present invention. (a) is a SEM image of a nickel-titanium alloy sample after femtosecond laser processing; (b) is a SEM image of a nickel-titanium alloy sample after femtosecond laser processing and alkali heat treatment; (c) is a SEM image of a nickel-titanium alloy sample after femtosecond laser processing, alkali heat treatment, polydopamine layer coating and antibacterial nanosilver loading.

[0033] Figure 3 The contact angle test results of the embodiments of the present invention are shown in Figure 1. (a) is the original polished nickel-titanium alloy surface, and (b) is the surface of the nickel-titanium alloy sample after femtosecond laser processing, alkali heat treatment, polydopamine layer coating and antibacterial nanosilver loading.

[0034] Figure 4The live-dead fluorescence microscopic images of osteoblasts (MC3T3-E1, after 24 hours of co-culture) of the modified biomedical titanium alloy material prepared in the embodiment of the present invention are shown in Figure 1. (a) shows the survival of osteoblasts on the surface of the original polished nickel-titanium alloy; (b) shows the survival of osteoblasts on the surface of the nickel-titanium alloy sample after femtosecond laser processing; (c) shows the survival of osteoblasts on the surface of the nickel-titanium alloy sample after femtosecond laser processing and alkali heat treatment; (d) shows the survival of osteoblasts on the surface of the nickel-titanium alloy sample after femtosecond laser processing, alkali heat treatment, polydopamine layer coating and antibacterial nanosilver loading.

[0035] Figure 5 The following are fluorescence microscopic images of osteoblast adhesion (MC3T3-E1, after 24 hours of co-culture) on the modified biomedical titanium alloy material prepared in the embodiment of the present invention. Among them, (a) is the osteoblast adhesion on the original polished nickel-titanium alloy surface; (b) is the osteoblast adhesion on the nickel-titanium alloy sample surface after femtosecond laser processing; (c) is the osteoblast adhesion on the nickel-titanium alloy sample surface after femtosecond laser processing and alkali heat treatment; (d) is the osteoblast adhesion on the nickel-titanium alloy sample surface after femtosecond laser processing, alkali heat treatment, polydopamine layer coating and antibacterial nanosilver loading.

[0036] Figure 6 The fluorescent microscopic images of Staphylococcus aureus colonization on the modified biomedical titanium alloy material prepared in the embodiment of the present invention. (a) is the colonization of Staphylococcus aureus on the surface of the original polished nickel-titanium alloy; (b) is the colonization of Staphylococcus aureus on the surface of the nickel-titanium alloy sample after femtosecond laser processing; (c) is the colonization of Staphylococcus aureus on the surface of the nickel-titanium alloy sample after femtosecond laser processing and alkali heat treatment; (d) is the colonization of Staphylococcus aureus on the surface of the nickel-titanium alloy sample after femtosecond laser processing, alkali heat treatment, polydopamine layer coating and loading of antibacterial nanosilver.

[0037] Figure 7 Fluorescence microscopic images of E. coli colonization on modified biomedical titanium alloy materials prepared in accordance with the embodiments of the present invention. (a) shows the E. coli colonization on the surface of the original polished nickel-titanium alloy; (b) shows the E. coli colonization on the surface of the nickel-titanium alloy sample after femtosecond laser processing; (c) shows the E. coli colonization on the surface of the nickel-titanium alloy sample after femtosecond laser processing and alkali heat treatment; (d) shows the E. coli colonization on the surface of the nickel-titanium alloy sample after femtosecond laser processing, alkali heat treatment, polydopamine layer coating and antibacterial nanosilver loading.

[0038] Among them, 1 represents a femtosecond laser; 2 represents a continuous attenuation plate; 3 represents a first reflector; 4 represents a second reflector; 5 represents an optical shutter; 6 represents a third reflector; 7 represents a focusing lens; 8 represents a nickel-titanium alloy material to be processed; 9 represents a six-degree-of-freedom translation stage; 10 represents a dichroic mirror; 11 represents a white light source; 12 represents a CCD camera; and 13 represents a computer. DETAILED DESCRIPTION

[0039] The present invention is described in detail below with reference to the accompanying drawings and embodiments.

[0040] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods.

[0041] Example 1

[0042] A biomedical titanium alloy surface modification method of this embodiment includes the following specific steps:

[0043] Step 1: A polished nickel-titanium alloy sample with a surface roughness of less than 5 angstroms was ultrasonically cleaned with deionized water and anhydrous ethanol solution at room temperature for 5 minutes.

[0044] Step 2: Blow dry the cleaned sample described in step 1 with an ear bulb to obtain a clean nickel-titanium alloy sample.

[0045] Step 3: Use Figure 1 The femtosecond laser processing system shown in the figure processes nickel-titanium alloy. Among them, 1-femtosecond laser; 2-continuous attenuation plate; 3-first reflector; 4-second reflector; 5-light shutter; 6-third reflector; 7-focusing lens; 8-nickel-titanium alloy material to be processed; 9-six-degree-of-freedom translation stage; 10-dichroic mirror; 11-white light source; 12-CCD camera and 13-computer; the laser generated by the femtosecond laser sequentially passes through the continuous attenuation plate, the first reflector, the second reflector, the light shutter, the third reflector, and the focusing lens, and is focused on the surface of the nickel-titanium alloy material to be processed; the computer controls the switch of the light shutter and the movement of the six-degree-of-freedom translation stage; the white light generated by the white light source sequentially passes through the dichroic mirror, the third reflector, and the focusing lens to irradiate the surface of the nickel-titanium alloy material to be processed, and is sequentially reflected along the focusing lens, the third reflector, and the dichroic mirror to the CCD camera to generate real-time imaging of the processing area. The laser processing parameters are specifically set as follows: the wavelength of the femtosecond laser is 800nm, the repetition frequency is 1000Hz, a 5x objective lens is used for processing, the aperture is limited so that the spot diameter is 5mm before the objective lens focuses, the laser power is 10mW, the scanning speed is 600μm / s, the scanning interval is 10um, processing is performed at the focus, and high-pressure nitrogen is used to blow away chips during the entire processing process to process large-area, consistent micro-nano structures.

[0046] Step 4: Prepare an alkaline solution with a concentration of 5M composed of sodium hydroxide and deionized water, place the alkaline solution and the sample prepared in step 3 into a high-pressure reactor lined with polytetrafluoroethylene, and cover it tightly. Then, place the high-pressure reactor in a muffle furnace, set the temperature rise program of the muffle furnace to maintain the reaction temperature at 80°, react for 24 hours, and clean and dry after the treatment.

[0047] Step 5: Select Tris buffer with a pH value of 8.5 as the solvent, prepare a dopamine hydrochloride solution with a concentration of 2 mg / mL of dopamine hydrochloride, then fully immerse the sample prepared in step 4 in the dopamine hydrochloride solution and let it stand for 24 hours. After the treatment, wash and dry.

[0048] Step 6: Prepare a 50 mM silver nitrate solution using deionized water as solvent, and place the sample prepared in step 5 into the silver nitrate solution. Allow to react for 6 hours at room temperature in the dark, and use the reducing property of polydopamine to reduce the silver ions to nanosilver particles that bind to the sample.

[0049] Step 7: Rinse the sample prepared in step 6 with deionized water, and dry it in a vacuum drying oven (37° C., 4 h) to obtain a modified biomedical titanium alloy material.

[0050] The biomedical titanium alloy modified surface prepared by the method of the present invention has good hydrophilicity, excellent resistance to bacterial infection and excellent ability to integrate with bone tissue, and can be used in medical devices such as bone implants to repair bone defects and treat postoperative bacterial infections.

[0051] like Figure 1 Shown is the optical path diagram of the processing method of the present invention.

[0052] like Figure 2 Shown are SEM images of the surface of the material prepared in the embodiment of the present invention. From Figure (a), it can be seen that after femtosecond laser processing, a groove structure with composite periodic corrugations is formed on the surface of the nickel-titanium alloy sample; from Figure (b), it can be seen that after alkali heat treatment, the alkali heat treatment does not destroy the groove structure with composite periodic stripes formed by the femtosecond laser processing, and a rich nanosheet structure is formed on this substrate, thereby obtaining a groove-micro-corrugation-nanosheet multi-level micro-nano composite structure; from (c), it can be seen that the polydopamine layer coating and antibacterial nanosilver loading did not damage the previous groove-micro-corrugation-nanosheet multi-level micro-nano composite structure substrate, and formed relatively evenly distributed nanoparticles thereon.

[0053] like Figure 3The static contact angle of the surface of the material prepared in the embodiment of the present invention is shown. It can be seen from the figure that the contact angle of the original polished nickel-titanium alloy surface is 74.6°, and the contact angle of the nickel-titanium alloy sample surface after femtosecond laser processing, alkali heat treatment, polydopamine layer coating and loading of antibacterial nanosilver is 12.3°, which has a strong ability to adsorb water molecules and good hydrophilicity, and can provide a good interface for cell adhesion.

[0054] like Figure 4 The fluorescent microscopic images of the in vitro cell live-death test of the modified biomedical titanium alloy material prepared in the embodiment of the present invention are shown, wherein (a) is the original polished nickel-titanium alloy surface; (b) is the surface of the nickel-titanium alloy sample after femtosecond laser processing; (c) is the surface of the nickel-titanium alloy sample after femtosecond laser processing and alkali heat treatment; (d) is the surface of the nickel-titanium alloy sample after femtosecond laser processing, alkali heat treatment, polydopamine layer coating and antibacterial nanosilver loading. It can be seen from the figure that the surface of each group of samples is a large area of ​​green fluorescence, no strong red fluorescence appears, and the cells on each group of materials are basically alive, indicating that the prepared materials are basically non-cytotoxic.

[0055] like Figure 5 The figure shows the adhesion characteristics of the modified biomedical titanium alloy material prepared in the embodiment of the present invention. It can be seen from the figure that compared with the original polished surface (a), the surface of the nickel-titanium alloy sample after femtosecond laser processing and alkali heat treatment (c) and the surface of the nickel-titanium alloy sample after femtosecond laser processing, alkali heat treatment, polydopamine layer coating and antibacterial nanosilver loading (d) are almost completely covered with osteoblasts with abundant pseudopodia, and the number of cells is also greatly increased compared with the original polished surface, indicating that the modified biomedical titanium alloy material prepared in the embodiment of the present invention has good biological activity, can promote the adhesion and proliferation of osteoblasts, and has excellent osteogenic properties and the ability to integrate with bone tissue.

[0056] like Figure 6The fluorescent microscopic image of Staphylococcus aureus colonization on the modified biomedical titanium alloy material prepared in the embodiment of the present invention is shown. The coverage rate of live bacteria (green) on the original polished surface (a) is 41.6%, and the coverage rate of dead bacteria (red) is 1.9%. Live Staphylococcus aureus is almost colonized on the entire sample surface, with only a small amount of inactivation. The coverage rate of live bacteria on the surface of the nickel-titanium alloy sample (b) after femtosecond laser processing is 36.0%, and the coverage rate of dead bacteria is 1.4%. The number of Staphylococcus aureus has decreased slightly. The coverage rate of live bacteria on the surface of the nickel-titanium alloy sample (c) after femtosecond laser processing and alkaline heat treatment is 24.1%, and the coverage rate of dead bacteria is 6.9%. It is observed that the number of Staphylococcus aureus is greatly reduced compared with the original surface, and the proportion of dead bacteria has increased, indicating that the groove-microripple-nanosheet multi-level micro-nano composite structure can greatly reduce the colonization sites of Staphylococcus aureus and has a certain bactericidal ability. The live bacteria coverage on the surface of the nickel-titanium alloy sample (d) after femtosecond laser processing, alkaline heat treatment, polydopamine layer coating and loading of antibacterial nanosilver was 0.1%, the dead bacteria coverage was 8%, and there was almost no live Staphylococcus aureus colonization.

[0057] like Figure 7 Shown is a fluorescent microscopic image of Escherichia coli colonization on a modified biomedical titanium alloy material prepared in accordance with an embodiment of the present invention. The coverage of live bacteria (green) on the original polished surface (a) is 44.7%, and the coverage of dead bacteria (red) is 0.5%, and the surface is evenly covered with Escherichia coli. The coverage of live bacteria on the surface of the nickel-titanium alloy sample (b) after femtosecond laser processing is 33.3%, and the coverage of dead bacteria is 0.8%, and the number of Escherichia coli colonization is reduced to a certain extent. The coverage of live bacteria on the surface of the nickel-titanium alloy sample (c) after femtosecond laser processing and alkaline heat treatment is 28.9%, and the coverage of dead bacteria is 0.5%, and the coverage of live bacteria is significantly reduced compared to the original polished surface, indicating that the three-level micro-nano composite of grooves-microripples-micropores shows that the structure has a certain effect in resisting Escherichia coli colonization. The live bacteria coverage on the surface of the nickel-titanium alloy sample (d) after femtosecond laser processing, alkaline heat treatment, polydopamine layer coating and loading of antibacterial nanosilver was 0.1%, the dead bacteria coverage was 5.7%, the number of Escherichia coli on the surface was extremely small, and there was almost no live Escherichia coli colonization.

[0058] The specific description above further illustrates the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above is only a specific embodiment of the present invention and is not limited to the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for surface modification of a biomedical titanium alloy, characterized in that: The steps include: Step 1, ultrasonically cleaning and drying the polished nickel-titanium alloy material; Step 2: focusing a femtosecond laser vertically onto the surface of the nickel-titanium alloy material for processing, and then ultrasonically cleaning and drying the material after processing to obtain a nickel-titanium alloy sample with a micron-submicron characteristic structure surface; Step 3, placing the nickel-titanium alloy sample obtained in step 2 into a high-temperature reaction kettle, adding alkali solution for alkali heat treatment, ultrasonic cleaning and drying to obtain a nickel-titanium alloy sample with a micron-submicron-nanometer characteristic structure surface; Step 4: placing the nickel-titanium alloy sample with a micron-submicron-nanometer characteristic structure surface obtained in step 3 into an alkaline Tris buffer containing dopamine hydrochloride to form a polydopamine coating thereon to obtain a composite structure; Step 5: placing the composite structure obtained in step 4 into a silver nitrate solution to generate nanosilver on the composite structure to obtain a silver-loaded composite structure; completing the surface modification.

2. A biomedical titanium alloy surface modification method as claimed in claim 1, characterized in that: The specific implementation steps of step 2 are as follows: (1) Loading a glass slide fixed with a clean nickel-titanium alloy material onto a high-precision six-degree-of-freedom translation stage; (2) A sapphire femtosecond laser processing system was selected, a 5x processing objective lens was selected, the femtosecond laser repetition rate was set to 1000 Hz, the femtosecond laser processing power was set to 8-30 mW, the scanning speed was 500-2000 um / s, the scanning interval was 8-20 um, and processing was performed at the focus. After processing, the sample was cleaned and dried to obtain a nickel-titanium alloy sample with a micron-submicron characteristic structure surface.

3. A biomedical titanium alloy surface modification method as claimed in claim 1, characterized in that: The specific implementation steps of step three are as follows: prepare an alkaline solution with a concentration of 1-5M composed of sodium hydroxide and deionized water, place the alkaline solution and the nickel-titanium alloy sample with a micron-submicron characteristic structure surface prepared in step two into a high-pressure reactor lined with polytetrafluoroethylene, and cover it tightly. Then, place the high-pressure reactor in a muffle furnace, set the reaction temperature to 80°, react for 12h-24h, clean and dry after the treatment, and obtain a nickel-titanium alloy sample with a micron-submicron-nanometer characteristic structure surface.

4. A biomedical titanium alloy surface modification method as claimed in claim 1, characterized in that: The specific implementation steps of step four are as follows: select an alkaline Tris buffer with a pH value of 8 to 10, and use it as a solvent to prepare a dopamine hydrochloride solution with a concentration of 1 mg / ml to 3 mg / ml; fully immerse the nickel-titanium alloy sample with a micron-submicron-nanometer characteristic structure surface prepared in step three in the dopamine hydrochloride solution and let it stand for 12h-24h, and wash and dry after the treatment.

5. A biomedical titanium alloy surface modification method as claimed in claim 1, characterized in that: The specific implementation steps of step five are as follows: prepare a silver nitrate solution with a concentration of 10mM-50mM, place the composite structure prepared in step four into the silver nitrate solution, and react for 1h-12h under light-proof conditions; after the treatment, wash and dry.

6. A biomedical titanium alloy surface modification method as claimed in claim 1, characterized in that: The obtained silver-loaded composite structure is used for bone defect repair and postoperative bacterial infection; the obtained silver-loaded composite structure has good hydrophilicity, promotes cell adhesion and proliferation, can improve the integration ability of biomedical titanium materials and bone tissue, and has the ability to resist bacterial infection.

7. A device for implementing the method according to any one of claims 1 to 6, characterized in that: include: Femtosecond lasers; Continuous attenuation sheet; a first reflector; a second reflector; Light shutter; A third reflector; Focusing lens; Nickel-titanium alloy material to be processed; Six-degree-of-freedom translation stage; dichroic mirror ; White light source; CCD camera and computer; the laser light generated by the femtosecond laser passes through a continuous attenuation plate, a first reflector, a second reflector, a light shutter, a third reflector and a focusing lens in sequence, and is focused on the surface of the nickel-titanium alloy material to be processed; the computer controls the opening and closing of the light shutter, the movement of the six-degree-of-freedom translation stage and displays the imaging generated by the CCD camera; the white light generated by the white light source passes through a dichroic mirror, a third reflector and a focusing lens in sequence to irradiate the surface of the nickel-titanium alloy material to be processed, and is reflected along the focusing lens, the third reflector and the dichroic mirror in sequence to the CCD camera to generate real-time imaging of the processing area.

Citation Information

Patent Citations

  • Dopamine-nanosilver composite coating and preparation method thereof

    CN102719824A

  • Titanium alloy containing antibacterial coating as well as preparation method and application thereof

    CN104357814A

  • Biomedical titanium surface modifying method

    CN105965154A

  • Titanium alloy implant with effects of resisting infection and promoting bone formation and preparation method thereof

    CN109453425A

  • Pyrolytic carbon surface self-organizing three-level micro-nano composite structure

    CN114473212A